2020
DOI: 10.3855/jidc.12741
|View full text |Cite
|
Sign up to set email alerts
|

Dual versus triple therapy for uncomplicated brucellosis: A retrospective cohort study

Abstract: Introduction: Brucellosis is a zoonotic disease caused by Brucella spp. affecting multiple body systems and may lead to complications. Saudi Arabia is a country where brucellosis is endemic. This study aimed to describe the epidemiological characteristics of uncomplicated brucellosis and to assess outcomes of different antibiotic regimens. Methodology: A retrospective cohort study in a Saudi tertiary academic medical center. Adults with confirmed uncomplicated brucellosis between January 2008 and Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A total of 2,537 papers were searched according to the search strategy. After removing duplicates and following the inclusion and exclusion criteria, we finally included 15 papers that were obtained from PubMed, Web of Science, CENTRAL, Embase, CNKI, and SinoMed databases in the meta-analysis (total of 1,466 patients and 35 treatment groups), consisting of 11 randomized controlled trials and 4 cohort studies [ 15 , 21 , 22 , 24 , 25 , 30 39 ]. Fig 1 shows the flow chart of the literature screening process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2,537 papers were searched according to the search strategy. After removing duplicates and following the inclusion and exclusion criteria, we finally included 15 papers that were obtained from PubMed, Web of Science, CENTRAL, Embase, CNKI, and SinoMed databases in the meta-analysis (total of 1,466 patients and 35 treatment groups), consisting of 11 randomized controlled trials and 4 cohort studies [ 15 , 21 , 22 , 24 , 25 , 30 39 ]. Fig 1 shows the flow chart of the literature screening process.…”
Section: Resultsmentioning
confidence: 99%
“…For acute brucellosis, a combination of doxycycline, rifampicin, and streptomycin can achieve a 100% cure rate [ 21 ]; no cases of relapse after combined treatment with doxycycline and rifampin plus aminoglycosides for osteoarthritic brucellosis [ 22 ]; long-term triple therapy is also effective in patients with spinal bone destruction caused by brucellosis [ 23 ]. However, it has also been found that triple antibiotic therapy has the same clinical effect as dual antibiotic therapy in the treatment of brucellosis [ 24 , 25 ]; despite the higher efficacy of triple antibiotic therapy, the former has a higher rate of side effects compared to the dual antibiotic therapy regimen [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another unique adverse effect that tetracyclines share with fluoroquinolones is photosensitivity [27]. Both tetracyclines and fluoroquinolones are also indicated in brucellosis, a condition that requires a prolonged duration of therapy of at least six weeks [28]. They also share the same drug interaction of potential chelation with divalent and trivalent cations contained in minerals and antacids; though, doxycycline is not significantly affected when co-administered with milk, unlike tetracycline [1].…”
Section: Discussionmentioning
confidence: 99%
“…Our study was limited by a few factors. The first was the small number of patients in the BL-D arm, which was attributed to the fact that doxycycline is commonly used for indications other than CAP, such as skin infections, vaginal infections, and brucellosis [ 18 ]. Second, some patients had insufficient data in their electronic medical records to determine clinical cure or failure; hence, they could not be included in the study.…”
Section: Discussionmentioning
confidence: 99%